Out-of-control criminal justice: the systems improvement solution for more safety, justice, accountability, and efficiency - Mears, Daniel P. (Cambridge University Press, 2017)
Introduction: out-of-control criminal justice -- Systems problems are not specific to crime and justice -- What is a system? -- The criminal justice system -- The systems improvement solution for safety, justice, accountability, and efficiency -- Benefits of the systems improvement solution and pitfalls to avoid in implementing it -- Conclusion: criminal justice under control